1978
DOI: 10.1346/ccmn.1978.0260503
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Series for Dioctahedral Smectites

Abstract: Abstract--Several dioctahedral clay minerals are related through reaction series. These series can be produced hydrothermally from beidellite gel and montmorillonite by making simple changes in interlayer and solution chemistry. The series are:gel-K-beidellite-random illite/smectite-K-rectorite-illite; K-montmorillonite-K-rectorite-illite; Na-montmorillonite or beidellite-Na-rectorite-paragonite; Li-montmorillonite-Li-tosudite-Li-rectorite-cookeite(?); Mg-montmorillonite-Mg-rectorite-tosu dite-sudoite(?); Ca-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
40
1

Year Published

1983
1983
1993
1993

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(50 citation statements)
references
References 43 publications
9
40
1
Order By: Relevance
“…The smectite layers are beidellitic. Very similar XRD reflections were reported by Eberl and Hower (1977) for a synthetic, ordered, interstratified illite/smectite with about 35% expandable layers, a material that was subsequently called K-rectorite (Eberl, 1978).…”
supporting
confidence: 71%
“…The smectite layers are beidellitic. Very similar XRD reflections were reported by Eberl and Hower (1977) for a synthetic, ordered, interstratified illite/smectite with about 35% expandable layers, a material that was subsequently called K-rectorite (Eberl, 1978).…”
supporting
confidence: 71%
“…Especially applicable to this study are those experiments conducted in the Na hydroxide systems (Barth-Wirshing and H/511er, 1989), where the starting material used was rhyolitic glass and the precipitation of analcime was observed. Experimental clay mineral transformations in shales have also been widely studied in the laboratory (Eberl, 1978;Velde, 1985;Whitney and Northrop, 1988). Directly applicable to this study is the work of Eberl (1978) and Matsuda and Henmi (1983) where the transformation of smectites and kaolinite to rectorite was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental clay mineral transformations in shales have also been widely studied in the laboratory (Eberl, 1978;Velde, 1985;Whitney and Northrop, 1988). Directly applicable to this study is the work of Eberl (1978) and Matsuda and Henmi (1983) where the transformation of smectites and kaolinite to rectorite was observed. The effects of high solution pH on silicate dissolution rates have been studied by Brady and Walther (1989), who showed that minerals in contact with high pH solutions have increased dissolution rates due to mineral surface speciation.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction mechanism for this charge increase has been discussed in several papers. Investigation ofdiagenetic clays and hydrothermal experiments (Eberl, 1976;Eberl and Hower, 1976) indicate Copyright 9 1991, The Clay Minerals Society a transformation in which AI 3+ substitutes for Si 4+ in the tetrahedral sheet, followed by interlayer potassiu m fixation and interlayer contraction. On the other hand, combined X-ray powder diffraction (XRD) and transmission electron microscopy (TEM) studies of dispersed illitic clays from bentonites and sandstones led Nadeau et a l. (1985) to propose a neoformation mechanism, i.e., a dissolution of smectite and precipitation/ growth of thin illite particles.…”
Section: Introductionmentioning
confidence: 99%